Ars Celebrandi Dalam Dokumen Desiderio Desideravi - Yusuf Silaban (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
This research was conducted in commemoration of the 60th anniversary of the Liturgical Document, Sacrosanctum Concilium (1963-2024). It is fitting that this moment is used to promote the liturgy, through the Desiderio Desideravi document. This article specifically explores the theme of Ars Celebrandi. For that purpose, this article is approached through a study of documents and literature. The results of the literature review are as follows: first, living in the post-modern with all its negative aspects, the faithful urged to stand firm in faith that true salvation comes from The Paschal Mystery of Christ. Second, the liturgy is the first and foremost place in which they celebrate His Mystery through the sacramental signs and symbols. Third, in celebrating the inestimable Mystery, the people of God are supported to realize the sense of ars celebrandi; celebrating the liturgy in faith, full, consciousness, and active participation, dedication, discipline, and elegancy. In keeping the sense of ars celebrandi, priests are reminded to not reduce liturgical celebration on a rubrical mechanism or creativity without rules, because the rite in itself is a norm, and the norm is never an end in itself, it is always at the service of a higher reality that it means to protect.